MOLECULAR DOCKING OF ANTIMYCIN A3 ANALOGS AND ITS AROMATIC SEGMENTS AS INHIBITORS OF APOPTOSIS PROTEIN MARKER BCL-XL AND MCL-1 - Arsianti, Ade; Fadilah, Fadilah; Erlina, Linda; Paramita, Rafika Indah (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Apoptosis is an important cellular process that causes the death of damaged cells. Its malfunction can lead to cancer development and poor response to conventional chemotherapy. Cellular proteins from the B-cell lymphoma 2 (BCL-2) family are crucial for apoptosis. Breast cancer is the most commonly diagnosed cancer among women worldwide. The aim of this work was to design using in silico docking antimycin A3, antimycin analogs, and its aromatic segments as inhibitors of Bcl-xl and Mcl-1. Methods: In silico molecular docking approach has been utilized to find the potential anticancer from antimycin A3 analogs and its aromatic segments. Antimycin A3 analogs and its aromatic segments were modeled into three-dimensional (3D) structures using Marvin Sketch. Based on Protein Data Bank, 3ZLN for Bcl-xl, and 5IEZ for Mcl-1 were selected as apoptosis protein marker from BCL-2 family. Geometry optimization and minimization of energy 3D structure of antimycin A3 analogs and segments (ligands) using the AutoDock software. Docking process and amino acid residue analysis were executed using AutoDock software. The best docking score was shown by the lowest binding energy and also checked with Lipinski rule of five. Results: In silico molecular docking showed antimycin A3 analogs, amide 5 and aromatic segment 14 have the best interaction and activity for Bcl-xl receptor inhibition. Moreover, amide 5 and segment 15 showed the best interaction and activity for Mcl-1 receptor inhibition. Conclusion: Our results clearly demonstrate that amide 5, segment 14, and segment 15 of antimycin A3 analog have a strong inhibitory activity against Bcl-xl and Mcl-1, and should be further developed as a promising candidate for the new anti-apoptosis agents. Â